2016
DOI: 10.1016/j.spa.2016.04.033
|View full text |Cite
|
Sign up to set email alerts
|

Localisation in the Bouchaud–Anderson model

Abstract: Abstract. It is well-known that both random branching and trapping mechanisms can induce localisation phenomena in random walks; the prototypical examples being the parabolic Anderson and Bouchaud trap models respectively. Our aim is to investigate how these localisation phenomena interact in a hybrid model combining the dynamics of the parabolic Anderson and Bouchaud trap models. Under certain natural assumptions, we show that the localisation effects due to random branching and trapping mechanisms tend to (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(48 citation statements)
references
References 24 publications
0
48
0
Order By: Relevance
“…More recently, it has been shown that for sufficiently heavy-tailed potentials (Pareto [11], exponential [12], Weibull [5,17]), the solution exhibits the strongest possible form of localisation: complete localisation. In [14] this was shown to also be the case for a model that replaced the Laplacian with the generator of a trapped random walk. By contrast, in very recent work [3] it has been shown that in the double-exponential case the PAM localises on a single connected island, rather than on a single site.…”
Section: Localisation In the Pammentioning
confidence: 87%
“…More recently, it has been shown that for sufficiently heavy-tailed potentials (Pareto [11], exponential [12], Weibull [5,17]), the solution exhibits the strongest possible form of localisation: complete localisation. In [14] this was shown to also be the case for a model that replaced the Laplacian with the generator of a trapped random walk. By contrast, in very recent work [3] it has been shown that in the double-exponential case the PAM localises on a single connected island, rather than on a single site.…”
Section: Localisation In the Pammentioning
confidence: 87%
“…In the sense of convergence in probability, concentration with n t D 1 was proved for some related potential distributions in [LacMör12,SidTwa14,FioMui14] (even in random environment, see [MuiPym14] and Sect. 7.9.2).…”
Section: Mass Concentrationmentioning
confidence: 99%
“…Recently [MuiPym14], the PAM was studied in another class of random environment, more precisely, the underlying random walk was replaced by the Bouchaud random walk, better known under the name Bouchaud trap model, where the randomness of the holding times does not sit in the bonds, but in the sites, and is chosen very heavy-tailed. More explicitly, the generator is given by…”
Section: Localisation In the Bouchaud-anderson Modelmentioning
confidence: 99%
See 2 more Smart Citations